The Effect of Transcutaneous Electric Nerve Stimulation (TENS) on Anxiety and Fear in Children Aged 9-14 Years - Nina Cebalo; Dubravka Negovetić-Vranić; Vanja Bašić Kes (University of Zagreb. School of Dental Medicine, 2020)
Introduction: Dental fear or dental phobia is caused by previous unpleasant dental experiences and pain. It can result in delaying or avoiding dental visits. Most often it leads to individuals avoiding visiting the dentist until physical pain completely impairs the quality of life. Objectives: Transcutaneous electrical nerve stimulation (TENS) is a method of pain relief involving the use of a mild electrical current. The main aim of this study was to examine whether the TENS device affects the reduction of anxiety and fear during dental procedures. Material and Methods: The study was conducted on a sample of 125 respondents, aged 9-14 years. Statistical significance of differences between pre- and post-treatment results on all applied measuring instruments was verified by the t-test for dependent samples. The calculation was performed for all respondents and individually for the three observed groups. The Children`s Fear Survey Schedule - Dental Subscale test was used to assess anxiety and fear. Results: The results on the CFSS-DS scale in all subjects did not differ statistically significantly before and after treatment (p > 0.05). The results on the CFSS-DS scale in subjects who received TENS were statistically significantly different before and after treatment (p < 0.01). The results on the CFSS-DS scale in subjects who received local anesthesia were statistically significantly different before and after treatment (p < 0.05). Conclusion: The TENS device had an anxiolytic effect after the first visit.